Β‐asarone inhibited cell growth and promoted autophagy via P53/Bcl‐2/Bclin‐1 and P53/AMPK/mTOR pathways in Human Glioma U251 cells. Issue 3 (30th August 2017) - Wang, Nanbu; Zhang, Qinxin; Luo, Laiyu; Ning, Baile; Fang, Yongqi
Abstract : Glioma is the most common type of primary brain tumor and has an undesirable prognosis. Autophagy plays an important role in cancer therapy, but it is effect is still not definite. P53 is an important tumor suppressor gene and protein that is closely to autophagy. Our aim was to study the effect of β‐asarone on inhibiting cell proliferation in human glioma U251 cells and to detect the effect of the inhibition on autophagy through the P53 signal pathway. For cell growth, the cells were divided into four groups: the model, β‐asarone, temozolomide (TMZ), and co‐administration groups. For cell autoghapy and the P53 pathway, the cells were divided into six groups: the model, β‐asarone, 3MA, Rapa, Pifithrin‐µ, and NSC groups. The counting Kit‐8 assay and flow cytometry (FCM) were then used to measure the cell proliferation and cycle. Electron microscopy was used to observe autophagosome formation. Cell immunohistochemistry/‐immunofluorescence, FCM and Western blot (WB) were used to examine the expression of Beclin‐1 and P53. The levels of P53 and GAPDH mRNA were detected by RT‐PCR. Using WB, we determined autophagy‐related proteins Beclin‐1, LC3‐II/I, and P62 and those of the P53 pathway‐related proteins P53, Bcl‐2, mTOR, P‐mTOR, AMPK, P‐AMPK, and GAPDH. We got the results that β‐asarone changed the cellular morphology, inhibited cell proliferation, and enhanced the expression of P53, LC3‐II/I, Beclin‐1, AMPK, and pAMPK while inhibiting the expression of P62, Bcl‐2, mTOR, and pmTOR. All the data suggested that β‐asarone could reduce the cell proliferation and promote autophagy possible via the P53 pathway in U251 cells. Abstract : β‐asarone inhibits the growth of glioma U251 cells. β‐asarone promotes autophagy of U251 cells. The autophagy process possible be promoted through the P53/Bcl‐2/Bclin‐1 and P53/AMPK/mTOR signal pathway.